PENGARUH DUAL TASK TRAINING TERHADAP KESEIMBANGAN DINAMIS PADA LANSIA - Stella Elsa Gratia Plena; Suhardi; Dwi Kurniawati (Jurnal Nasional Fisioterapi, 2024)
Background: Elderly is the final stage of human development and a person who has reached the age of more than 60 years. The aging process in the elderly causes functional vulnerabilities including in maintaining dynamic balance. The role of physiotherapy in inhibiting the speed of functional disorders in the elderly can be done through the provision of dual task training interventions, which are exercises designed to combine cognitive and motor tasks that are carried out at one time (simultaneously) to improve the ability to perform dual tasks and improve dynamic balance, namely walking. Objective: To determine the effect of dual task training on dynamic balance in the elderly. Method: the research method in the form of an experimental with a one-group research design with control pretest and posttest design was carried out in December 2023 – January 2024. The subjects in this study, namely 60 elderly people who met the inclusion and exclusion criteria, were divided into two groups, namely 30 subjects in the treatment group and 30 subjects in the control group. The measuring tool used in this study is the time up and go test (TUGT). Results: based on the results of the statistical test using the paired sample t-test, the result was p=0.000 (p<0.05) which means that there is an effect after being given dual task training on dynamic balance in the elderly, And the results of the different test of the treatment group and the control group using an independent sample T-test obtained a result of p=0.033 (p<0.05), meaning that there was a difference between the treatment group and the control group on walking ability in the elderly. Conclusion: Dual Task Training (motor-cognitive) significantly affects the dynamic balance of the elderly so as to improve the ability to walk in the elderly.